How prevalent are financial conflicts of interest in dermatology randomized controlled trials? A cross‐sectional study. (17th March 2021) - Steele, L.; Earp, E.; Hong, A.
Summary: Since the last assessment of conflicts of interest (COIs) in dermatology randomized controlled trials (RCTs) in 2004, several countries have introduced transparency databases. We assessed the prevalence of financial COIs in dermatology RCTs and quantified payments from study sponsors to academic/clinical authors using transparency databases, which are available in the USA, France, Australia, Belgium and the Netherlands, while the UK has a noncompulsory transparency database. We included RCTs from the top 10 dermatology journals and the top 7 general medical journals published in 2019. The study assessed 83 RCTs, and COIs were identified in 69%. The highest prevalence was in exclusively industry‐funded trials (46/47, 98%), which consisted of personal payments to an academic/clinical author (96% of trials) and having authors who were employees/stockholders (96%). Payments were identified for 31/56 (55%) academic/clinical first/final authors (median payment US$28 746, maximum US$597 299, interquartile range US$17 061–146 253), and 24/31 payments (77%) payments were each > US$10 000.